Pengalaman Guru Kelas V dalam Menerapkan Pembelajaran Berdiferensiasi di SD 3 Jepang Kudus - Saerdilla Nawafela; Indi Musfirotul Untsa; Salsa Eka Indriyani; Muhammad Faris Ananta R; Finna Fakhriyah; Erik Aditia Ismaya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Differentiated instruction is an approach aimed at meeting students' learning needs based on their abilities, characteristics, and requirements. This study aims to describe the experiences of a fifth-grade teacher in implementing differentiated instruction at SD 3 Jepang Kudus. The study employs a qualitative approach using a phenomenological design. Data were collected through interviews, observations, and documentation, and subsequently analyzed using the Miles and Huberman model, which encompasses data reduction, data display, and conclusion drawing. Data validity was established through technique triangulation. The results indicate that the teacher perceives differentiated instruction as an effort to provide learning support tailored to students' needs. Implementation is carried out through adjustments to the learning process, guidance, peer tutoring, and the creation of an inclusive learning environment. This implementation has a positive impact on students' academic, social, and emotional development. Challenges encountered include the diversity of students' learning abilities and the suboptimal application of differentiation regarding learning products and assessments. These findings underscore the importance of teacher experience in optimally and sustainably accommodating students' learning needs.